1999
DOI: 10.1046/j.1460-9568.1999.00786.x
|View full text |Cite
|
Sign up to set email alerts
|

1‐Aminoindan‐1,5‐dicarboxylic acid and (S)‐(+)‐2‐(3′‐carboxybicyclo[1.1.1] pentyl)‐glycine, two mGlu1 receptor‐preferring antagonists, reduce neuronal death in in vitro and in vivo models of cerebral ischaemia

Abstract: Metabotropic glutamate (mGlu) receptors have been implicated in a number of physiological and pathological responses to glutamate, but the exact role of group I mGlu receptors in causing postischaemic injury is not yet clear. In this study, we examined whether the recently-characterized and relatively selective mGlu1 receptor antagonists 1-aminoindan-1,5-dicarboxylic acid (AIDA) and (S)-(+)-2-(3'-carboxybicyclo[1.1.1]pentyl)-glycine (CBPG) could reduce neuronal death in vitro, following oxygen-glucose deprivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 79 publications
6
103
1
Order By: Relevance
“…Neuroprotective effects of Bv8 (PK2) in mixed murine cortical cultures and rat organotypic hippocampal slices exposed to oxygen and glucose deprivation (OGD) Bv8 can be used as a suitable pharmacological tool to investigate the effects of PK2 in vitro and in vivo (Giannini et al, 2009;Severini et al, 2015). To investigate the possible neuroprotective effects of Bv8 we carried out experiments in cultured murine cortical cells exposed to OGD, an in vitro model of focal cerebral ischemia routinely used in our lab (Pellegrini-Giampietro et al, 1999a). We have demonstrated that OGD induces necrotic neuronal death in this system, as detected by the appareance of necrotic ultrastructural features 24 h later and the lack of caspase-3 activation (Moroni et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Neuroprotective effects of Bv8 (PK2) in mixed murine cortical cultures and rat organotypic hippocampal slices exposed to oxygen and glucose deprivation (OGD) Bv8 can be used as a suitable pharmacological tool to investigate the effects of PK2 in vitro and in vivo (Giannini et al, 2009;Severini et al, 2015). To investigate the possible neuroprotective effects of Bv8 we carried out experiments in cultured murine cortical cells exposed to OGD, an in vitro model of focal cerebral ischemia routinely used in our lab (Pellegrini-Giampietro et al, 1999a). We have demonstrated that OGD induces necrotic neuronal death in this system, as detected by the appareance of necrotic ultrastructural features 24 h later and the lack of caspase-3 activation (Moroni et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Cultures of mixed murine cortical cells were exposed to oxygenglucose deprivation (OGD) as previously described in detail (Pellegrini-Giampietro et al, 1999a, 1999b. Briefly, culture medium was replaced by a glucose-free balanced salt solution saturated with 95% N2/5% CO2 and heated to 37 C. Multiwells were then sealed into an airtight incubation chamber equipped with inlet and outlet valves and 95% N2/5% CO2 was blown through the chamber for 10 min to ensure maximal removal of oxygen.…”
Section: Oxygen-glucose Deprivation (Ogd) In Cortical Cell Culturesmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted, however, that OGD exposure in the present study was much milder (40 vs. 60 min) and that PARP inhibitors are known to be efficacious only when excitotoxic or ischemic insults are particularly intense and presumably necrotic (Bonfoco et al, 1995;Meli et al, 2004). In cultured cortical cells, DHPG by itself is not toxic but exacerbates LDH release and neuronal damage following exposure to OGD (Pellegrini-Giampietro et al, 1999a). Our results show that DPQ was able to completely abolish the component of OGD injury evoked by DHPG, strongly suggesting that PARP overactivation is responsible for the neuronal damage evoked by DHPG in this model.…”
Section: Discussionmentioning
confidence: 52%